PENGEMBANGAN MEDIA E-ENSIKLOPEDIA PADA SUB TOPIK BAGAIMANA BERNAPAS MEMBANTUKU MELAKUKAN AKTIVITAS SEHARI-HARI - Wardah Aqila; Rita Istiana; Yuli Mulyawati (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This study develops an E-Encyclopedia for the sub-topic "How Breathing Helps Me Perform Daily Activities" within the IPAS subject to enhance interactive learning. Using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the research was conducted at SD Negeri Citeureup 03, Bogor, involving three experts as validators and 34 fifth-grade students. Data collection included observation, interviews, questionnaires, and documentation, with qualitative and quantitative analysis. Results showed significant improvement in students' understanding, with an N-Gain score of 67% and increased pretest (76) and posttest (93) scores. Expert validation confirmed the media's high feasibility, receiving positive feedback from teachers and students. The E-Encyclopedia effectively enhances the quality of science education by making learning more interactive and engaging.